2023
DOI: 10.1038/s41389-022-00446-y
|View full text |Cite
|
Sign up to set email alerts
|

AKT1 regulates UHRF1 protein stability and promotes the resistance to abiraterone in prostate cancer

Abstract: Oncogenic activation of PI3K/AKT signaling pathway, together with epigenetic aberrations are the characters of castration-resistant prostate cancer (CRPC). UHRF1 as a key epigenetic regulator, plays a critical role in prostate cancer (PCa) development, and its expression is positively correlated with the degree of malignancy. In this present study we investigated the potential regulatory mechanism of AKT1 on UHRF1, and further validated the in vitro and in vivo anticancer efficacy of AKT phosphorylation inhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…S8F). Using a previously established pair of parental or Abi-refractory lines 22RV1/22RV1-R ( 46 ), we showed that 22RV1-R (versus parental AR-high 22RV1) exhibited a preferential sensitivity to SP1i (fig. S8G), highlighting an enhanced dependency of SP1 in CRPC cells.…”
Section: Resultsmentioning
confidence: 99%
“…S8F). Using a previously established pair of parental or Abi-refractory lines 22RV1/22RV1-R ( 46 ), we showed that 22RV1-R (versus parental AR-high 22RV1) exhibited a preferential sensitivity to SP1i (fig. S8G), highlighting an enhanced dependency of SP1 in CRPC cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the regulatory roles in cell cycle, our laboratory has recently reported that AKT1 [ 31 ], by inducing the phosphorylation of threonine 210 of UHRF1, maintains the protein stability of UHRF1 (Fig. 1 ).…”
Section: Ptms Of Uhrf1 Proteinmentioning
confidence: 99%
“…For example, AKT1-induced UHRF1 phosphorylation (UHRF1-T210) inhibits the ubiquitination of UHRF1. Phosphorylation of AKT1 promotes the USP7-induced deubiquitination of UHRF1, while concurrently inhibiting the SCFβ-TrCP-mediated protein ubiquitination of UHRF1, which leads to the resistance of PCa cells to abiraterone [ 31 ]. M phase-specific kinase CDK1/cyclin B induces the phosphorylation of UHRF1 at S652, thereby reducing the interaction between UHRF1 and USP7, redu c ing the USP7-mediated deubiquitination of UHRF1 and promoting protein degradation, consequently inhibiting cell proliferation [ 28 ].…”
Section: Crosstalk Between Ptms Of Uhrf1mentioning
confidence: 99%
“…Some AR inhibitors, such as enzalutamide and abiraterone (CYP17A1 inhibitor), have been approved by the FDA for the treatment of advanced stage PCa ( Rodriguez-Vida et al, 2015 ). However, some cases develop resistance to enzalutamide and abiraterone, making the disease almost incurable ( Wang and Liu, 2020 ; Fu et al, 2023 ). Unfortunately, in most cases AR becomes again active, and these patients relapse ( Sowalsky et al, 2015 ).…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%